Influence of profile on fire performance of cold-formed galvanised iron built-up section with bolted connection under standard fire temperature - Sam, Varun Sabu; Anand, N.; EL Hachem, Chady; Abdallah, Mirvat; Azab, Marc (Frontiers in Built Environment, 2025)
This paper aims to investigate the flexural behavior of Galvanized Iron (GI) based CFS built-up beams with lipped channels and lipped channel with different stiffener arrangements when exposed to prolonged periods of elevated temperature. Seven built-up beam specimens, each consisting of two lipped channel profiles placed back-to-back, are fastened with self-driving screws in the webs and tested for four point bending experimentally. Following the heating process, two distinct cooling methods were employed to return them to room temperature. The flexural behavior, ultimate moment capacity and moment-deflection curves of tested CFS built-up beams are discussed. Sections cooled using water demonstrate more deformation compared to those cooled using air. Notably, the beam section heated for 90 min and cooled using water showed a deformation of 2.62 mm, representing 1.84 times increase compared to the reference section. Detailed finite element (FE) models were developed and calibrated against the experimental results. They were then employed for a parametric study. Parametric analysis is conducted to study the flexural behavior of two additional types of CFS built-up sections. These include two back-to-back lipped channels with different web stiffeners, in comparison with a basic built-up section consisting of lipped channels. The cross-sectional area of all three sections is identical. The comparison of results reveals that the built-up section consisting of lipped channels with type II web stiffeners have the highest moment-carrying capacity among all profiles for all durations of heating and cooling. Among the unheated sections, the moment capacity of the built-up section with type II web stiffeners is 42.49% and 46.28% higher than that of the reference section and the built-up section with type I web stiffeners, respectively. This study provides practical insights for structural applications, emphasizing the influence of stiffeners and cooling methods on the performance of CFS beams under fire exposure. Additionally, it evaluates the applicability of the Direct Strength Method (DSM) in AISI specifications, offering potential refinements to design codes for CFS built-up sections subjected to elevated temperatures.